Evaluation of Voluntary Feed Intake and Digestibility Organic Feed Ingredients for Adult Female Goats - Diningrat, Sriwulan Cakrawati; Irfan, Mohamad; Ismail, Mohammad; Mustafa, Mustafa; Nirwana, Nirwana; Zainal, Zainal; Amam, Amam (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
Limited forage for livestock during the dry season has an impact on low livestock productivity, so a source of feed other than grass is needed as an effort to utilize local resources.The purpose of research is voluntary feed intake level and organik matter digestibility adult female goat given by 3 different feed.  It was carried out on experimental farm of Hasanuddin University for 3 months. A total of six a head of adult male goats aged around 1.5 years with preliminary weights 11-15 kg were used and place at individual pen of 100 x 50 x 100 cm with 80 cm above ground level. This research was designed using RBSL with 3 treatments and it was used 2 heads of goat replication. The feed treatment covered 3 kinds of leaves, namely mango (R1), jackfruit (R2), and banana (R3). The voluntary feed intake (kg/day) was measured based on difference between given and remained feed weights.  The measurement of feed digestibility (%) using Total Collecting Method, covering total of feed comsumption and total of goat faeces (24 hours) separeted with urine. The research result showed that the voluntary feed intake level R1 leaves was heigher than R2 and R3 leaves, whereas the level of crude fiber digestibility and crude fat of R1 higher than  R2  and R3, but digestibility of crude protein R3 higher than R1 dan R2.